(untitled) (American Journal of Islam and Society, 2012)
Several novels have appeared after the September 11 attacks which deal directly or indirectly with the effect of the event on individuals, both inside and outside the United States. Though, the novels often claim to deal with the posttraumatic aftermath of the incident, the writers regularly use Orientalist stereotyping, and it seems that after September 11 these attitudes toward Muslims and Arabs have hardened and even strengthened the old Orientalist discourse. This paper shall focus on Don Delillo’s Falling Man and John Updike’s Terrorist because both novels were New York Times bestsellers and both novelists are prominent figures in American literature. It attempts to examine the way in which the novelists have responded to the September 11, 2001 attacks and how Muslims and their ideologies are represented. The significant point is that though these novels have been written in the twenty-first century, where there has been an increase in contacts and information about Muslims, the writers often use the same cliches and stereotypes about Muslims that have existed since the Middle Ages.